Alat Sensor Berbasis Internet Of Things (IoT) dalam Meningkatkan Pengetahuan Monitoring Kelembaban Lingkungan Fisik Rumah Penderita TB Paru - Chandra, Emilia; Zunidra, Zunidra; Ariyadi, Bambang; Kasjono, Heru Subaris; Purwanti, Nunuk Sri (Journal of Telenursing (JOTING), 2024)
This research aims to analyze the effectiveness of internet of things (IoT) based sensor devices in increasing knowledge of monitoring the humidity of the physical environment in the homes of pulmonary TB sufferers. The research method used by Research and Development uses a quasi-experimental approach. The initial step was to test the normality of the data using the Shapiro-Wilk statistical test. It was found that the data was not normally distributed, so the statistical test used a non-parametric test, namely the Wilcoxon test. The p value will be considered significant if the p value <0.05. The results of the research show that the field test, a p value of 0.000 <0.05 was obtained, meaning that there was a difference in the average user knowledge score before the intervention was carried out and after the intervention was carried out. The research conclusion is that Internet of Things (IoT) based sensor devices have proven effective in increasing knowledge of monitoring the humidity of the physical environment in the homes of pulmonary TB sufferers. Keywords: Sensor devices, Internet of Things (IoT), Knowledge of monitoring humidity in the physical environment of the home, Pulmonary TB